Investigation of the Relationship Between Intensive Care Nurses’ Attitudes Towards Obese Patients and Caring Behaviors - ÇELİK, MELİKE (My University, 2022)
Introduction-Aim: The aim of the study is to examine the relationship between the attitudes of intensive care nurses towards obese patients and caring behaviors. Method: This descriptive-relational study was conducted with 204 nurses working in intensive care units of a city hospital in October 2022. Data were collected using an online questionnaire using the Introductory Information Form, the Obesity Prejudice Scale (OPS), and the Caring Behaviors Inventory (CBI). Results: The mean age of the nurses was 26.17±2.35, and 95.1%of them were undergraduates. The intensive care unit experience period was 2.39±1.88 years. 81.9%of the nurses loved their profession. It was determined that 62.7%of the nurses did not want to care for obese patients and 52.9%did not receive training on obesity. 94.1%of the nurses stated that they had difficulties while giving care to obese patients. The OPS mean score of the nurses was 86.37±8.53, 38.2%were found to be biased and 59.8% were biased. A statistically significant negative correlation was found between OPS total score and age (p=0.045). The mean score of the CBI was 5.38±0.56, and it was determined that the nurses’ perceptions of the quality of care were high. The sub-dimension score of the scale’s assurance was higher in nurses who wanted to care for obese patients compared to nurses who did not want to care for obese patients(p=0.032). In our study, a significant relationship was not found between CBI and OPS. Conclusion: It was found that almost all of the intensive care nurses were prejudiced and prone to prejudice against obese patients, and their perceptions about the quality of care were high. It was determined that obesity bias levels were not effective in caring behaviors. This suggests that professional values rather than prejudices are effective in the care behaviors of intensive care nurses toward obese patients, who love their profession. Anahtar Kelimeler: intensive care, nurse, obesity, prejudice, caring behaviours
Keywords: intensive care; nurse; obesity; prejudice; caring behaviours